Bridging the Wastewater Treatment Gap in Rural India: A Decentralized Circular Economy Solution - Bhardwaj, Monika; Goel, Manisha (Journal of Economics and Management, 2026)
India is facing major challenges with sewage and wastewater management. Around 62 billion liters are generated, of which only 37% go under treatment. In Haryana villages, this issue is critical, as on one side their people are facing water scarcity as 60% of farmlands depend on rainfall. This paper presents a Hari Pravah model i.e., a decentralized and cost-effective approach for wastewater treatment focusing on resource recovery and circular economy fundamentals. The Hari pravah, planned for Banchari a Haryana Village, based on a hybrid sewage treatment plant with primary, secondary and tertiary treatment reaching 100% waste utilization. This model generates three revenue streams i.e. treated water for irrigation, organic fertilizers and biogas for energy. This strategy helps in increasing crop yields by 15-20%, and reduces CO2 emissions by 2.7 tons per ton of biomethane. It also generates job and entrepreneurial opportunities for villagers, encouraging rural development and resource recovery. The Hari Pravah model provides an expandable and sustainable method for wastewater management in growing economies, highlighting the importance of decentralized and resource directed methods.